MENGAJAR BERBICARA BAHASA INGGRIS DENGAN DIALOG UNTUK SEKOLAH MENENGAH PERTAMA DARUDDA'WAH - Masrurah, Atiya; Yolanda, Alvina; Ismu Purwaningsih, Dewi (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
The research aims to evaluate how well the dialogue method improves English speaking skills for class IX students at Darudda'wah Middle School. The research method used is quasi-experimental. This research was conducted at Darudda'wah Punggur Kecil Middle School. The study sample included 11 students in the experimental group and 10 students in the control group. The experimental group is the group that carries out learning using the dialogue method, while the control group is the group that carries out learning without the dialogue method. Based on the results of the t-test on post-test data for the experimental and control classes with a significance level of 0.05%, tcount > ttable (2,689 > 1,812), it can be concluded that in the experimental group, there were differences in teaching English-speaking between before and after the treatment. This means that the dialogue method is effective in teaching English speaking.